The Role Of Political Parties With The Worker Movement Rejecting The Omnibus Job Creation Law - Yarnes Imanuel Foni; Phil Aditya Perdana (Unram Law Review, 2022)
This study aims to determine the role of political parties in the worker's movement to reject the ratification of the omnibus law on Job Creation. The approach used is qualitative. This research relies on primary data collection mainly obtained through interviews with resource persons or key informants. Data were collected in two ways. The first is to conduct a literature study and content analysis of various literature and reports in the print media related to research problems, and secondly, by conducting interviews with resource persons. The role of political parties in the rejection of the Job Creation Law must straighten out the functions first, rights, and obligations of political parties according to the provisions of the current political law in Indonesia. Political parties' functions, rights, and obligations have been outlined in Law Number 2 of 2011 concerning Political Parties. The function of political parties is regulated in 11. One of the functions related to the context that we are talking about is Article 11, point 2 subpoint (a), which states that political parties function as a means of: "Increasing the political participation of members and the community to organize political and governmental activities." In addition, the role of the community, especially the laborers, in rejecting Indonesia's Omnibus Law (Law No. 11 of 2020 on Job Creation) is important for the suitability of government policies. It is stated in Presidential Regulation Number 68 of 2005 concerning Procedures for Preparing Draft Laws, Draft Government Regulations in Lieu of Laws, Draft Government Regulations, and Draft Presidential Regulations, particularly in Chapter VIII Article 41.